ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PENJUMLAHAN DAN PENGURANGAN BERDASARKAN TEORI NEWMAN - Titis Puspita Maharani; Sherin Himatussabrina Azzahra; Lovika Ardana Riswari (STKIP Subang, 2025)
Mathematics is the study of number concepts and counting operations, such asaddition and subtraction. In learning mathematics, student errors are often found,especially in story problems that involve understanding and applying theseoperations. The purpose of this study was to analyze student errors in solvingaddition and subtraction story problems based on Newmans theory. This studyused a qualitative descriptive approach with a population of 27 students of grade ISD N 1 Dersalam and the sample in this study were 3 students who showed thelowest scores in the diagnostic test. Data analysis techniques according to Milesand Huberman were carried out through observation, documentation, andinterviews. In this study, researchers used Newmans Theory to analyze students'errors in solving mathematics story problems. The stages include five stages thatare the basis of student errors, namely reading, understanding, transformation,process skills, and writing the final answer. The results of the analysis showed thateach of the 3 students experienced different errors, including inaccuracy inunderstanding the story problem, difficulty in transforming the problem sentenceinto mathematical form, and lack of accuracy in compiling and writing the finalanswer. The errors were caused by limitations in reading skills, studentsdifficulties in transforming the problem into mathematical form, and students lackof understanding of the story problem.